Shifting Meaning: Islamic Philanthropy According to the View of Muhammadiyah - Ahmad Rezy Meidina; Zaimudin Al-Mahdi Mokan (Universitas Darussalam Gontor, 2023)
This paper discusses Islamic philanthropy from the view of Muhammadiyah, this was obtained because there was a shift in the meaning of philanthropy in the past. Experts _ stated that philanthropy is an important element in Islam. Among the forms of philanthropy in Islam is zakat, one of Islam’s five pillars. Among other forms of Islamic philanthropy are infaq, alms, and waqf. Therefore philanthropy has a major position in the life of Muslims. The meaning above is different from philanthropy which is known in today's society but does not reduce the substance of philanthropy itself. Islam has an important role in terms of spreading religion and knowledge, establishing educational institutions, and even in the field of welfare. One important vehicle for the spread of Islam is the mosque, which was built on philanthropy. The Prophet Muhammad set an example of philanthropic behavior by establishing a mosque. Apart from establishing mosques, educational institutions which are places to gain knowledge were also established on the basis of philanthropy. It is through these educational institutions that the dissemination of knowledge develops. This paper aims to provide an understanding to the general public regarding the shift in the meaning of Islamic philanthropy, through the view of Muhammadiyah as the primary data source. The conclusion in this paper uses the theory of changes in Islamic law and uses a normative approach, of course with the aim of trying to reveal the values of truth in Islamic philanthropic practices in society so that they should be actualized in the future.Keywords: Islamic Philanthropy, Muhammadiyah, Theory of change in Islamic law